A non parametric survival analysis of business demography dynamics in Portugal - Nunes, Alcina (2010)
This article addresses the post-entry performance of Portuguese firms, using survival and hazard functions, along a period of eighteen years, from 1985 to 2007. The method follows the “Manual on Business Demography Statistics” (OECD/Eurostat, 2007), so as to assure international comparability with other datasets, such those from the Entrepreneurship Indicators Programme (OECD/Eurostat 2008 and 2009). In the exercise, we use a sub-set of the Quadros de Pessoal dataset (Employment Administrative Records by the Portuguese Ministry of Labour and Social Security), where only active employer enterprises are considered. The survival analysis is then disaggregated in different dimensions, namely sectors, regions and size class.